Improvements in Patient‐Reported Outcome Measures and Range of Motion After Rotator Cuff Repair, Superior Capsular Reconstruction, and Tendon Transfer May Not Necessitate Increases in Acromiohumeral Interval for Massive or Irreparable Rotator Cuff Tears: A Systematic Review - Rodrigo Saad Berreta; Juan Bernardo Villarreal‐Espinosa; Tomas F. Vega; Udit Dave; Kaitlyn Joyce; Cadence Lee; Garrett R. Jackson; Zeeshan Khan; Salvador Ayala; Johnathon McCormick; John P. Scanaliato; Nikhil N. Verma (Arthroscopy, 2026)
Purpose To perform a systematic review investigating the relation between improvements in patient‐reported outcomes and range of motion with changes in acromiohumeral interval (AHI) after rotator cuff repair (RCR), tendon transfer (TT), and superior capsular reconstruction (SCR) for massive or irreparable rotator cuff tears. Methods A literature search was performed using 3 databases from inception to December 2023 according to the 2020 Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines. Human clinical studies reporting changes in AHI after RCR, SCR, and TT for massive or irreparable rotator cuff tears were included. A qualitative comparison across studies that reported either statistically significant improvement or no significant improvement in AHI to patient‐reported outcomes and range of motion was conducted. Study quality was assessed using the Cochrane Collaboration's risk of bias tool and the Methodological Index for Non‐Randomized Studies criteria. Results Forty‐two studies including 1868 patients (362 RCR, 1101 SCR, and 405 TT) across 60 individual cohorts (10 RCR, 39 SCR, and 11 TT) were identified. Forty‐four cohorts (8 RCR, 31 SCR, and 5 TT) representing 1374 patients noted a statistically significant improvement in AHI ranging from 0.40 to 5.3 mm. Sixteen cohorts (2 RCR, 8 SCR, and 6 TT) representing 494 patients noted no statistically significant improvement in AHI ranging from −3.2 to 0.7 mm. The mean improvement from baseline to final follow‐up across American Shoulder and Elbow Surgeons, University of California‐Los Angles, Visual Analog Scale Pain, and Constant scores in addition to forward flexion were comparable across both groups. Conclusions Improvements in functional outcome measures and forward flexion after soft tissue reconstruction for massive or irreparable rotator cuff tears are observed regardless of whether the AHI increases significantly from baseline. Level of Evidence Level IV, systematic review of Level II to IV studies.